Palynological Study of the Genus Valerianella Miller (Valerianaceae) in Kurdistan Region-Iraq. - Sardar, Abdullah Shakur; Hussein, Shelan A. Aziz; Al-Dabbagh, Serwan Taha (Sulaimani Journal for Pure and Applied Sciences, 2015)
The present study dealt with the pollen grains of 11 species of the genus Valerianella Miller within the family Valerianaceae which have been collected within the field trips during spring and summer season of year 2014 (about 20 trips) from the different districts in Kurdistan of Iraq. From the used characters that had a role in the separation of some species were the pollen shapes, sizes, surface sculpture and the end shapes of the colpi, generally the pollens had a limited role in the species separation. Photographs have been taken for the polar and equatorial views of the pollen grains. The species were Valerianella chlorostephana Boiss., V. coronata (L.) DC., V. dactylophylla Boiss. & Hohen, V. discoidea (L.) Lois., V. kotschyi Boiss., V. lasiocarpa (Stev.) Betcke, V.muricata (Stev.) Baxt., V.oxyrhyncha Fisch & Mey, V.pumila (L.) DC., V. tuberculata Boiss. and V. vesicaria (L.) Moench.
Keywords: Palynological Study; Valerianella; Valerianaceae; Kurdistan; Iraq